Modalities of renal replacement therapy in acute kidney injury - Ileana Peride; Mirela Tiglis; Tiberiu Paul Neagu; Ana-Maria Nechita; Andrei Niculae; Ionel Alexandru Checherita (Romanian Journal of Medical Practice, 2021)
Impaired renal function artificial support development massively contributed to increased life expectancy and quality of life improvement. The first steps in this direction were made in the beginning of the 1900s, nowadays existing a variety of methods of renal replacement therapies that could be customized to each patient depending on the associated complications and comorbidities. Considering these aspects and that acute kidney injury (AKI) could represent a life-threatening condition, the present review will present different options of renal replacement therapies suitable to be initiated in emergency.